Millennial Leadership Style of Public Services in The Society 5.0 Era - Dwi Indah Yuliani Solihin; Asna Aneta (Publik : (Jurnal Ilmu Administrasi), 2021)
This article aims to analyze and describe the millennial leadership style for public services in the era of society 5.0. The method used in this article is a qualitative descriptive method. This method refers to the identification or characteristics that distinguish groups of people, objects and events. The results of the article show that 1) The challenges of public service in the era of society 5.0 provide great opportunities for millennials to lead bureaucratic organizations. Because millennials are seen as far more competitive, creative, critical, and idealistic in leading bureaucratic organizations than their seniors, Generation Y; 2) The millennial character is very close to digitalization adaptation so that it provides opportunities for government collaboration with the industrial sector; 3) In 2030 it is estimated that 70 percent of future leaders in Indonesia will come from the millennial generation who are at a productive age. This generation is in control of the Indonesian economy in the future and is expected to be able to lead this nation towards a more advanced and dynamic development. This article provides an illustration that millennial opportunities to become leaders need to be encouraged so that they are able to become exemplary leaders, leaders who have a sense of responsibility, and leaders who are able to take risks and work in teams.